KEEFEKTIFAN MODEL (TGT) BERBANTU MEDIA PERMAINAN ULAR TANGGA TERHADAP HASIL BELAJAR SDN GENUKSARI 01 SEMARANG - Harum Sulistyoningrum; Iin Purnamasari; Zainal Arifin (Jurnal Sinektik, 2018)
The purpose of this study was to determine the effectiveness of the media-assisted game team tournament model for snake and ladder games, my dream theme on the learning outcomes of fourth grade students of SDN genuksari 01 semarang.  Research results as follows. 1) the average student learning outcomes in the great subtheme of my dream is still low, while the completeness criteria is at least 65, 2) at the time of learning the student plays alone, talks with a peer, and does not listen to the teacher, 3) the model and media used teachers sometimes make students become bored so that the student are in passive and crowded learning themselves.There is a difference in student learning outcomes before and after using the model of the assisted tournament snake ladder game team game as evidenced by tcount 0,0624 > 2,04. Individual learning completeness posttest scores better than pretest scores. Classical learning completeness reach 90%.